The Effect of Incentives, Work Motivation and Work Environment on Employee Performance at PT Telang Agro Mandiri - Wati, Bungsu Widias; Helmi, Sulaiman; Trisninawati, Trisninawati; Noviardy, Andrian (International Journal of Marketing & Human Resource Research, 2026)
This study aims to analyze the influence of incentives, work motivation, and work environment on employee performance at PT. Telang Agro Mandiri. The background of this study is the importance of optimizing human resources by providing incentives and enhancing work motivation to support employee productivity. The study employs a quantitative approach, administering a survey to 102 employees. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares (PLS). The study's results indicate that incentives and work motivation significantly affect employee performance, whereas the work environment does not. These findings confirm that at PT. Telang Agro Mandiri, incentives, and work motivation are the primary factors in driving performance, while the work environment has not yet had a tangible impact. This study contributes to management in developing more targeted and effective human resource policies.